UJI AKTIVITAS ENZIM SELULOLITIK DARI BEKICOT (Achatina fulica) PADA BEBERAPA SUBSTRAT LIMBAH PERTANIAN - Muhammad Akbar Hasibuan; Fajar Restuhadi; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study to determine interaction of some agricultural waste substrate with incubation time using crude extract of cellulolytic enzyme extracted from snail (Achatina fulica). This study used a randomized block design (RAK) in factorial pattern with two factors. The first factor was the time (W) incubation with four levels. The second factor was the type of substrate, namely agricultural wastes (L) which comprises four types. From both these factors retrieved 16 treatment and each treatment was repeated three times, so the retrieved data 48 units of the experiment. Data were analyzed statistically using ANOVA (Analysis of Variance). If F counted was greater or equal than to F table then the analysis continued by Duncan's New Multiple Range Test (DNMRT) at 5% level. The results of the protein crude extract of cellulolytic enzyme         1.712 mg/ml enzyme. The results of the highest glucose levels on a banana peel waste substrate interaction with the incubation time 180 minutes is                457.00 mg/100 ml. The highest enzyme activity result in the interaction of banana peels waste substrate with incubation time 180 minutes is 0.45 U/ml. Keywords: Cellulolytic enzyme crude extract of snail (Achatina fulica), agricultural waste substrate, and incubation time